Gtsaṅ mz Źaṅ źuṅ gi Bon khod gsaṅ ba drag chen gyi sgrub pa las tshogs bcas kyi gsuṅ pod : a collection of texts from the rediscoveries of Dpon-gsas Khyuṅ-rgod-rtsal concerned with the Bonpo deities of the Ge-khod cycle and their propitiation - Dpon-gsas Khyuṅ-rgod-rtsal, b. 1175 (s.n.] ; distributor, Tibetan Bonpo Monastic Centre, 1973)
Rituals for the propitiation of the Ge-khod deities, protectors of Bon, believed to reside on Mt. Kailas in western Tibet.